Digital Transformation in Physics Education: A Systematic Review of Technology-Enhanced Learning Environments - Yusmita, Yesi; Tanjung, Lailatul Syifa; Henjilito, Raffly (Journal of Foundational Learning and Child Development, 2026)
Purpose of the Study: This systematic review investigates the integration of digital technologies into physics education across secondary and tertiary institutions globally, identifying patterns, outcomes, and evidence-based best practices within technology-enhanced learning environments (TELEs) from 2015 to 2024. Materials and Methods: Following PRISMA 2020 guidelines, a comprehensive electronic search was conducted across six major databases—Web of Science (WoS), Scopus, ERIC, IEEE Xplore, PsycINFO, and Google Scholar—using systematically constructed Boolean search strings. Inclusion criteria comprised peer-reviewed empirical studies published in English between January 2015 and December 2024, focusing on digital technology interventions in physics education contexts. After full screening, 87 studies met the inclusion criteria and were subjected to qualitative synthesis and descriptive meta-analysis. Results: Analysis revealed five dominant technology clusters: virtual laboratories and simulations (34.5%), augmented and virtual reality environments (21.8%), adaptive learning systems and AI-assisted instruction (18.4%), gamification platforms (14.9%), and collaborative online environments (10.3%). Studies consistently reported positive effects on conceptual understanding (mean effect size d = 0.67, 95% CI [0.54, 0.80]), student engagement (d = 0.72), and laboratory skill acquisition (d = 0.58). Emerging technologies such as immersive VR and AI-driven personalization demonstrated the highest effect sizes, particularly in abstract concept visualization and formative assessment. Conclusions: Digital transformation presents substantial pedagogical opportunities for physics education, provided that implementation is theoretically grounded, teacher-mediated, and contextually tailored. Critical barriers including digital inequity, teacher preparedness, and evidence gaps in long-term retention require urgent targeted policy and research attention.